Pendidikan Remaja dalam Perspektif Syekh Musthofa Al-Ghalayaini: Kajian Analisis Terjemahan Kitab Idzatun Nasyi’in - Rusmiyati; Matori; Zainal Abidin (Universitas Muhammadiyah Magelang, 2026)
This research aims to analyze the concept of youth education that has been conveyed by Sheikh Musthofa Al-Ghalayaini through a study of the book Idzatun Nasyi'in. The focus of this research is to reveal educational values, principles of character development, and their relevance to the education of today's teenagers. This research uses a qualitative approach method with the type of library research. The main data source is the book Idzatun Nasyi'in and its translation, while secondary data comes from relevant literature such as books, journals, articles and documents related to research. Data analysis techniques are carried out through text identification, theme classification, and inductive interpretation of meaning. Apart from that, this research also emphasizes the importance of moral education as the main foundation in forming teenagers' personalities with character and responsibility. The educational values contained in the book are not only theoretical, but also applicable in everyday life. The results of the research show that the concept of education according to Sheikh Musthofa Al-Ghalaya emphasizes the formation of morals, strengthening faith, self-control and social responsibility. These values are very relevant to the challenges of modern adolescent education which tends to experience a moral crisis. Therefore, Sheikh Musthofa Al-Ghalaya's thoughts can be used as a basis for developing character education based on Islamic values.